Analysis of Family Support and Knowledge of Hypertension Patients with Drug Compliance in Posbindu Sentralsari Village and East Central Village Toili District, Banggai District - Priyanto, Kurniawan Edi; Siti Naisah (Journal of Global Research in Public Health, 2023)
Hypertension is a chronic disease and is a major risk factor for  Hypertensive patients must have compliance in order to avoid various risks of other diseases. The purpose of this study is to analyze the relationshipfamily support and knowledge of hypertension sufferers with medication adherence in Posbindu Sentralsari Village and East Sentral Village, Toili District, Banggai Regency. In this study using a correlational analytic design with a cross sectional approach.The sample is some of the pre-elderly and elderly hypertension sufferers in Posbindu, Sentralsari Villageand East Central VillageToili District, Banggai Regency in January 2022 as many as 80 respondents, sampling method using simple random sampling technique. Data collection by using a questionnaire. Bivariate analysis using the Spearman Rank statistical test with a significant level of = 0.05. The results of the study showed that from 80 respondents. Many as 35 respondents (43.8%), most of the respondents had less knowledge as many as 47 respondents (58.8%) and almost half of the respondents were obedient to taking hypertension medication as many as 38 respondents (47, 5%).The results of data analysis using the Spearman Rank statistical test obtained P value < 0.05 (0.000 < 0.05) which meansthere isconnectionfamily support and knowledge of hypertension sufferers with medication adherence in Posbindu Sentralsari Village and East Sentral Village, Toili District, Banggai Regency. Lack of family support and the level of knowledge of hypertension sufferers who are less will affect non-compliance in taking hypertension medication, while good family support and good knowledge of hypertension sufferers will affect compliance in taking hypertension medication.